Biosecurity : understanding, assessing, and preventing the threat - Burnette, Ryan, 1977- (John Wiley & Sons, Inc., 2013)
"This book defines the concepts of biosecurity, biosafety, and biosurety and shows how they relate to one another under the overall framework of biodefense. The book also addresses biosecurity strategies for non-laboratory settings, including private sector facilities, the transportation infrastructure, and the food and agriculture sector including insurance, healthcare, the global supply chain, and agriculture. Discussions also include bioterrorism, biosecurity operations, various existing biosecurity programs, and biosecurity ethics. Designed to reach a wide variety of professionals, this resource provides a balanced and accessible look at biodefense and its applications"--